Passivation layer, preparation method thereof and perovskite solar cell
By using new interface modification materials to form a passivation layer in perovskite solar cells, the stability problems caused by perovskite surface defects are solved, and the effect of improving photovoltaic performance and stability is achieved.
Patent Information
- Application Number
- CN202411966890.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
AI Technical Summary
Perovskite solar cells have stability problems. The bare ions that are not coordinated on the perovskite surface are prone to polarization reactions, resulting in interface defects and light absorbing layer degradation, affecting device stability and performance.
A new type of interface modification material is used, including substances of specific chemical formulas such as 1-naphthol, 2,3-dihydroxynaphthalene, etc., to reduce defects on the perovskite surface by forming a passivation layer and improve the stability of the perovskite layer.
It effectively improves the photovoltaic performance and stability of perovskite solar cells, reduces preparation costs, and simplifies the process flow.
Smart Images

Figure CN119836122A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photovoltaics, and in particular relates to a passivation layer, a preparation method thereof and a perovskite solar cell. Background Art
[0002] After more than a decade of development, perovskite solar cells are currently in the process of commercialization. However, perovskite solar cells have stability issues, which is a key technical point that needs to be solved urgently. Specifically, uncoordinated exposed ions on the perovskite surface are prone to polarization reactions during the preparation process and the use of the device, resulting in interface defects, inducing degradation of the perovskite light-absorbing layer, and ultimately causing the device to gradually fail. Studies have shown that interface engineering in perovskite solar cells has a huge impact on the device. Reducing non-radiative carrier recombination at the surface / interface and increasing carrier lifetime are effective ways to optimize perovskite solar cells. Among them, interface passivation is a simple, effective, and easy-to-commercialize method in interface engineering.
[0003] The prior art uses cyclodextrin, ammonium salt and trifluoropropylbis(aziridine) compounds as interface modification materials. When cyclodextrin is used as the interface modification material, in order to enhance the contact between cyclodextrin and the perovskite layer, the surface of the perovskite layer needs to be micro-etched, which increases the preparation cost; when ammonium salt is used as the interface modification material, the surface of the perovskite layer is treated with ammonium salt to form a two-dimensional perovskite layer to reduce surface defects, but the two-dimensional perovskite layer affects the charge extraction and transmission at the interface to a certain extent, which may have an adverse effect on the device performance. When trifluoropropylbis(aziridine) compounds are used as the interface modification material, the passivation cost is high.
[0004] Therefore, there is an urgent need to develop a new type of low-cost interface modification material to improve the quality of the perovskite layer, thereby improving the photovoltaic performance and stability of perovskite solar cells. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides an interface modification material. The interface modification material of the present invention is an interface modification material corresponding to Formula A or Formula B. The interface modification material of the present invention has a simple structure and low cost; it can improve the photovoltaic performance and stability of perovskite solar cells.
[0006] Specifically, the present invention provides a passivation layer, wherein the passivation layer comprises an interface modification material, and the chemical formula of the interface modification material is shown in Formula A and / or Formula B:
[0007]
[0008] In formula A, R1 is a hydrogen atom, an amino group, a substituted or unsubstituted C1-C5 alkoxy group, a substituted or unsubstituted C1-C5 alkyl group, a cyano group, a sulfonic acid group, a hydroxyl group, a boric acid group, a halogen or a carboxyl group, R2 is a hydrogen atom, a halogen, a sulfonic acid group or an amino group, R3 is a hydrogen atom, an amino group, a halogen or a substituted or unsubstituted C1-C5 alkyl group, R4 is a hydrogen atom, an alkoxy group, a halogen or a hydroxyl group, R5 is a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group, a nitroso group, a hydroxyl group, an acetyl group, an amino group or a halogen, R6 is a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group, an ester group, a carboxyl group or a hydroxyl group, and R7 is a hydrogen atom, a halogen, an amino group or a substituted or unsubstituted C1-C18 alkyl group; in formula B, R8 is a hydrogen atom, a hydroxyl group or an amino group, R9 is a hydrogen atom or a substituted or unsubstituted C1-C18 alkoxy group, R 10 is a hydrogen atom, a sulfonic acid group, a hydroxyl group or a halogen, R 11 is a hydrogen atom, a nitro group, an acetyl group or a halogen, R 12 is a hydrogen atom, a carboxyl group, a hydroxyl group or a sulfonic acid group, R 13 is a hydrogen atom, a substituted or unsubstituted C1-C18 alkyl group, a substituted or unsubstituted C1-C18 alkoxy group, an amino group, a halogen group or an aldehyde group, and R 14 It is a hydrogen atom, a hydroxyl group or a sulfonic acid group.
[0009] In one or more embodiments, the interface modification material is selected from one or more of 1-naphthol, 2,3-dihydroxynaphthalene, 5-methyl-2-naphthol, 2-naphthol-6-sulfonic acid, 2-hydroxy-3-naphthoic acid, 2-hydroxy-6-naphthoic acid, 1-nitroso-2-naphthol, 1-bromo-2-naphthol, 1,6-dibromo-2-naphthol, 4-chloro-1-naphthol and 1-amino-2-naphthol-4-sulfonic acid.
[0010] In one or more embodiments, the thickness of the passivation layer is 1-10 nm.
[0011] The invention provides a method for preparing the passivation layer of the invention, the method comprising: mixing an interface modification material and a solvent to obtain a passivation layer precursor solution, coating the passivation layer precursor solution, and then annealing to obtain the passivation layer.
[0012] In one or more embodiments, the concentration of the interface modification material is 0.5-2 mg / mL.
[0013] In one or more embodiments, the solvent is an anti-solvent selected from one or more of isopropanol, ethanol, ethyl acetate and diethyl ether.
[0014] In one or more embodiments, the coating method is spin coating.
[0015] In one or more embodiments, the annealing temperature is 80-100°C.
[0016] In one or more embodiments, the annealing time is 5-10 min.
[0017] The present invention provides a perovskite solar cell comprising the passivation layer of the present invention.
[0018] In one or more embodiments, the perovskite solar cell further includes a perovskite layer and an electron transport layer, and the passivation layer is between the perovskite layer and the electron transport layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the structure of perovskite solar cells according to some embodiments of the present invention. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0021] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0022] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0023] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0024] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0025] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0026] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0027] The present invention provides a passivation layer comprising an interface modification material, wherein the chemical formula of the interface modification material is as shown in Formula A and / or Formula B:
[0028]
[0029] In formula A, R1 is a hydrogen atom, an amino group, a substituted or unsubstituted C1-C5 alkoxy group, a substituted or unsubstituted C1-C5 alkyl group, a cyano group, a sulfonic acid group, a hydroxyl group, a boric acid group, a halogen or a carboxyl group, R2 is a hydrogen atom, a halogen, a sulfonic acid group or an amino group, R3 is a hydrogen atom, an amino group, a halogen or a substituted or unsubstituted C1-C5 alkyl group, R4 is a hydrogen atom, an alkoxy group, a halogen or a hydroxyl group, R5 is a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group, a nitroso group, a hydroxyl group, an acetyl group, an amino group or a halogen, R6 is a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group, an ester group, a carboxyl group or a hydroxyl group, and R7 is a hydrogen atom, a halogen, an amino group or a substituted or unsubstituted C1-C18 alkyl group; in formula B, R8 is a hydrogen atom, a hydroxyl group or an amino group, R9 is a hydrogen atom or a substituted or unsubstituted C1-C18 alkoxy group, R 10 is a hydrogen atom, a sulfonic acid group, a hydroxyl group or a halogen, R 11 is a hydrogen atom, a nitro group, an acetyl group or a halogen, R 12 is a hydrogen atom, a carboxyl group, a hydroxyl group or a sulfonic acid group, R 13 is a hydrogen atom, a substituted or unsubstituted C1-C18 alkyl group, a substituted or unsubstituted C1-C18 alkoxy group, an amino group, a halogen group or an aldehyde group, and R 14 It is a hydrogen atom, a hydroxyl group or a sulfonic acid group. The interface modification material of the present invention has a simple molecular structure and low cost; wherein the benzene ring can be used as a Lewis base to form a Lewis adduct with a specific Lewis-type defect, thereby reducing or capturing trace I2 present as an electronic defect in the perovskite, passivating the perovskite defects, and improving the efficiency of the perovskite solar cell; the -OH group can effectively passivate the positive and negative charge defects and lead clusters, improve the stability of the perovskite layer, and thus improve the photoelectric performance and stability of the perovskite solar cell.
[0030] In the present invention, the interface modification material can be one or more of 1-naphthol, 2,3-dihydroxynaphthalene, 5-methyl-2-naphthol, 2-naphthol-6-sulfonic acid, 2-hydroxy-3-naphthoic acid, 2-hydroxy-6-naphthoic acid, 1-nitroso-2-naphthol, 1-bromo-2-naphthol, 1,6-dibromo-2-naphthol, 4-chloro-1-naphthol and 1-amino-2-naphthol-4-sulfonic acid. In the present invention, the use of the above-mentioned interface modification materials can effectively improve the photoelectric performance and stability of perovskite solar cells.
[0031] In the present invention, the thickness of the passivation layer may be 1-10 nm, for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, and 10 nm.
[0032] The invention provides a method for preparing the passivation layer of the invention, the method comprising: mixing an interface modification material and a solvent to obtain a passivation layer precursor solution, coating the passivation layer precursor solution, and then annealing to obtain the passivation layer.
[0033] In the present invention, the concentration of the interface modification material can be 0.5-2 mg / mL, such as 0.5 mg / mL, 1 mg / mL, 1.5 mg / mL, 2 mg / mL. In the present invention, controlling the concentration of the interface modification material within the above range can effectively improve the photoelectric performance and stability of the perovskite solar cell.
[0034] In the present invention, the solvent may be an anti-solvent, and the anti-solvent may be one or more selected from isopropanol, ethanol, ethyl acetate and ether. In the present invention, the coating method may be spin coating.
[0035] In the present invention, the annealing temperature may be 80-100° C., such as 80° C., 85° C., 90° C., 95° C., 100° C. In the present invention, the annealing time may be 5-10 min, such as 5 min, 6 min, 7 min, 8 min, 9 min, 10 min.
[0036] The present invention provides a perovskite solar cell comprising the passivation layer of the present invention. The perovskite solar cell of the present invention further comprises a perovskite layer and an electron transport layer, and the passivation layer is between the perovskite layer and the electron transport layer.
[0037] In the present invention, the chemical formula of the perovskite structure material is ABX3; A can be a monovalent cation, including but not limited to a cesium ion (Cs + ), rubidium ion (Rb + ), methylamine ion (CH3NH3 + , MA), dimethylamine ion and formamidine ion (CH(NH2)2 + , FA) in one or more; B can be a divalent cation, including but not limited to lead ions (Pb2+ ), copper ions (Cu 2+ ), zinc ion (Zn 2+ ), gallium ions (Ga 2+ ), tin ions (Sn 2+ ) and calcium ions (Ca 2+ ) in one or more; X may be a monovalent anion, including but not limited to iodide ion (I - ), bromide ion (Br - ), chloride ion (Cl - ), fluoride ion (F - ) and thiocyanate ion (SCN - )
[0038] In the present invention, the thickness of the perovskite layer can be 100-1000 nm, for example, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm.
[0039] In the present invention, the perovskite solar cell may include an inverted single junction perovskite solar cell or an inverted stacked perovskite solar cell. In the present invention, the inverted single junction perovskite solar cell may include a conductive substrate, a hole transport layer, a perovskite layer, a passivation layer, an electron transport layer and an electrode layer in sequence. In the present invention, the inverted stacked perovskite solar cell may include a bottom electrode, a bottom cell, a tunneling layer, an inverted perovskite top cell and a top electrode in sequence, and the inverted top cell may include a hole transport layer, a perovskite layer, a passivation layer and an electron transport layer in sequence. In the present invention, a hole blocking layer may also be present between the electron transport layer and the electrode layer. In the present invention, the conductive substrate may include a substrate and a transparent metal oxide (TCO) conductive layer, the substrate may be glass, and the transparent metal oxide conductive layer may be indium tin oxide (ITO).
[0040] In the present invention, the material of the hole transport layer may be selected from inorganic, polymer and small molecules. In the present invention, the material of the electron transport layer may be selected from one or more of [6,6]-phenyl-C61-butyric acid methyl ester, C60 and tin oxide. In the present invention, the material of the hole blocking layer may be 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) or zirconium acetylacetonate. In the present invention, the material of the electrode layer may be selected from one or more of silver, copper, transparent metal oxide and carbon electrode.
[0041] The method for preparing an inverted single-junction perovskite solar cell of the present invention comprises:
[0042] (1) depositing a hole transport layer on the surface of a conductive substrate;
[0043] (2) depositing a perovskite layer on the surface of the hole transport layer;
[0044] (3) depositing an electron transport layer on the surface of the perovskite layer;
[0045] (4) Depositing an electrode layer on the surface of the electron transport layer to obtain an inverted single-junction perovskite solar cell.
[0046] The method for preparing an inverted stacked perovskite solar cell of the present invention comprises:
[0047] (1) depositing a bottom electrode and a tunneling layer on both sides of the bottom cell;
[0048] (2) depositing a hole transport layer on the surface of the tunneling layer;
[0049] (3) depositing a perovskite layer on the surface of the hole transport layer;
[0050] (4) depositing an electron transport layer on the surface of the perovskite layer;
[0051] (5) A top electrode is deposited on the surface of the electron transport layer to obtain an inverted stacked perovskite solar cell.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] (1) The interface modification material of the present invention has a simple molecular structure and low cost;
[0054] (2) In the interface modification material of the present invention, the benzene ring can act as a Lewis base to form a Lewis adduct with a specific Lewis-type defect, thereby reducing or capturing trace I2 present as an electronic defect in the perovskite, passivating the perovskite defects, and improving the efficiency of the perovskite solar cell; the -OH group can effectively passivate the positive and negative charge defects and lead clusters, improve the stability of the perovskite layer, and thereby improve the photoelectric performance and stability of the perovskite solar cell.
[0055] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.
[0056] Example 1
[0057] This embodiment prepares a perovskite solar cell, which specifically includes the following steps:
[0058] (1) The ITO conductive glass was ultrasonically cleaned with deionized water, acetone and isopropanol for 15 minutes respectively, and dried in a drying oven at 75° C. for later use; the dried ITO conductive glass was treated in an ultraviolet ozone machine for 25 minutes to remove organic impurities on its surface and optimize its surface wettability to obtain a clean conductive substrate;
[0059] (2) dissolving 1 mg of (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid in 1 mL of isopropanol to prepare a hole transport material solution, coating the hole transport material solution on a conductive substrate, and then annealing at 100° C. for 10 minutes to form a hole transport layer;
[0060] (3) Dissolve 722.08 mg of lead iodide and 238.50 mg of iodomethylamine solid in 1 mL of N,N-dimethylformamide (DMF), and stir at 25°C until completely dissolved to obtain a perovskite precursor solution; in a nitrogen glove box, take 30 μL of the perovskite precursor solution and drop it onto the surface of the hole transport layer, first spin-coat it at 1000 rpm for 10 s, then spin-coat it at 5000 rpm for 30 s, and quickly drop 125 μL of chlorobenzene at 25 s during this process, and then place it on a hot stage for heating and annealing at 100°C for 40 min to form a perovskite layer with a thickness of 500 nm;
[0061] (4) dissolving 5 mg of 1-naphthol as an interface modification material in 5 mL of ether, stirring at 25° C. in the dark until dissolved, to obtain a passivation layer precursor solution, taking 100 μL of the passivation layer precursor solution and dynamically spin coating and depositing it on the surface of the perovskite layer at a speed of 3000 rpm for 30 seconds, and then annealing at 50° C. for 30 minutes to crosslink the passivation molecules, to obtain a passivation layer with a thickness of 6 nm;
[0062] (5) 20 mg of [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) was dissolved in 1 mL of chlorobenzene and stirred at 25 °C to obtain a [6,6]-phenyl-C61-butyric acid methyl ester solution. 30 μL of the [6,6]-phenyl-C61-butyric acid methyl ester solution was taken and spin-coated on the surface of the passivation layer at 3000 rpm for 60 s to form an electron transport layer with a thickness of 30 nm.
[0063] (6) dissolving 0.5 mg of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) in 1 mL of isopropanol and stirring at 25° C. to obtain a hole blocking layer solution; dropping 40 μL of the hole blocking layer solution onto the electron transport layer and spin coating at 5000 rpm for 35 s to form a hole blocking layer with a thickness of 6 nm;
[0064] (7) The conductive substrate formed with the hole blocking layer, electron transport layer, passivation layer, perovskite layer, and hole transport layer is transferred to a vacuum coating instrument and the vacuum degree is drawn to 3×10-4 Silver was evaporated at 400 Å / min to form an electrode layer with a thickness of 100 nm on the hole blocking layer, and a perovskite solar cell was obtained at the same time.
[0065] Example 2
[0066] The other steps of this embodiment are the same as those of Embodiment 1, except that the interface modification material of this embodiment is 2,3-dihydroxynaphthalene.
[0067] Example 3
[0068] The other steps of this embodiment are the same as those of Embodiment 1, except that the interface modification material of this embodiment is 5-methyl-2-naphthol.
[0069] Example 4
[0070] The other steps of this embodiment are the same as those of Embodiment 1, except that the interface modification material of this embodiment is 2-naphthol-6-sulfonic acid.
[0071] Example 5
[0072] The other steps of this embodiment are the same as those of Embodiment 1, except that the interface modification material of this embodiment is 2-hydroxy-6-naphthoic acid.
[0073] Example 6
[0074] The other steps of this embodiment are the same as those of Embodiment 1, except that the interface modification material of this embodiment is 1,6-dibromo-2-naphthol.
[0075] Example 7
[0076] The other steps of this embodiment are the same as those of Embodiment 1, except that the interface modification material of this embodiment is 4-chloro-1-naphthol.
[0077] Example 8
[0078] The other steps of this embodiment are the same as those of Embodiment 1, except that the amount of the interface modification material added in this embodiment is 2.5 mg, and the thickness of the passivation layer obtained is 1 nm.
[0079] Example 9
[0080] The other steps of this embodiment are the same as those of Embodiment 1, except that the amount of the interface modification material added in this embodiment is 10 mg, and the thickness of the passivation layer obtained is 10 nm.
[0081] Comparative Example 1
[0082] The other steps of this comparative example are the same as those of Example 1, except that this comparative example does not contain a passivation layer.
[0083] Comparative Example 2
[0084] The other steps of this comparative example are the same as those of Example 1, except that 1 mg of 1-naphthol is added to the perovskite precursor solution and no passivation layer is included in this comparative example.
[0085] Comparative Example 3
[0086] The other steps of this comparative example are the same as those of Example 1, except that in this comparative example, 1 mg of 2,3-dihydroxynaphthalene is added to the perovskite precursor solution and no passivation layer is included.
[0087] Comparative Example 4
[0088] The other steps of this comparative example are the same as those of Example 1, except that 1 mg of 5-methyl-2-naphthol is added to the perovskite precursor solution and no passivation layer is included in this comparative example.
[0089] Comparative Example 5
[0090] The other steps of this comparative example are the same as those of Example 1, except that 1 mg of 2-naphthol-6-sulfonic acid is added to the perovskite precursor solution and no passivation layer is included in this comparative example.
[0091] Comparative Example 6
[0092] The other steps of this comparative example are the same as those of Example 1, except that 1 mg of 2-hydroxy-6-naphthoic acid is added to the perovskite precursor solution and no passivation layer is included in this comparative example.
[0093] Comparative Example 7
[0094] The other steps of this comparative example are the same as those of Example 1, except that 1 mg of 1,6-dibromo-2-naphthol is added to the perovskite precursor solution and no passivation layer is included in this comparative example.
[0095] Comparative Example 8
[0096] The other steps of this comparative example are the same as those of Example 1, except that 1 mg of 4-chloro-1-naphthol is added to the perovskite precursor solution and no passivation layer is included in this comparative example.
[0097] Comparative Example 9
[0098] The other steps of this comparative example are the same as those of Example 1, except that the amount of the interface modification material added in this comparative example is 20 mg, and the thickness of the passivation layer obtained is 16 nm.
[0099] Test Case
[0100] Photovoltaic performance test of perovskite solar cells: At 25°C and AM 1.5G standard solar spectrum, a solar simulator was used to set the voltage range to -0.1-1.20V, and the current output of the perovskite solar cells prepared in Examples 1-9 and Comparative Examples 1-9 at different voltages was tested, and the corresponding current-voltage (IV) characteristic curves were plotted, where the cell surface area was 0.05cm 2 , the incident light power (Pin) is 100mW / cm 2 The photoelectric performance (open circuit voltage, short circuit current density, fill factor and initial photoelectric conversion efficiency) of the perovskite solar cells prepared in Examples 1-9 and Comparative Examples 1-9 were obtained according to the characteristic curves.
[0101] Stability test of perovskite solar cells: The perovskite solar cells prepared in Examples 1-9 and Comparative Examples 1-9 were placed at 100°C for 200 hours and then tested for photoelectric conversion efficiency. The stability of the perovskite solar cell can be obtained by combining the tested aging photoelectric conversion efficiency with the normalized efficiency = aging photoelectric conversion efficiency / initial photoelectric conversion efficiency × 100%.
[0102] (1) Open circuit voltage (Voc): The voltage value corresponding to when the current is equal to zero.
[0103] (2) Short-circuit current density (Jsc): The current value when the voltage is zero is the short-circuit current (Isc), and the current per unit battery surface area is the short-circuit current density.
[0104] (3) Fill factor (FF): The ratio of the maximum output power (Pmax) of the battery to the product of the open circuit voltage and the short circuit current. The calculation formula is (Pmax / Voc*Isc), where the maximum power point is the point where the battery output power reaches its maximum value.
[0105] (4) Photoelectric conversion efficiency (PCE): Photoelectric conversion efficiency refers to the ratio of maximum output power to incident light power (Pin), and the calculation formula is (Pmax / Pin)*100%.
[0106] The test results of the open circuit voltage, short circuit current density, fill factor, initial photoelectric conversion efficiency and normalized efficiency of the perovskite solar cells prepared in Examples 1-9 and Comparative Examples 1-9 are shown in Table 1.
[0107] Table 1: Open circuit voltage, short circuit current density, fill factor, initial photoelectric conversion efficiency and normalized efficiency of perovskite solar cells prepared in Examples 1-9 and Comparative Examples 1-9
Claims
1. A passivation layer, characterized in that: The passivation layer comprises an interface modification material, and the chemical formula of the interface modification material is shown in Formula A and / or Formula B: In formula A, R1 is a hydrogen atom, an amino group, a substituted or unsubstituted C1-C5 alkoxy group, a substituted or unsubstituted C1-C5 alkyl group, a cyano group, a sulfonic acid group, a hydroxyl group, a boric acid group, a halogen or a carboxyl group, R2 is a hydrogen atom, a halogen, a sulfonic acid group or an amino group, R3 is a hydrogen atom, an amino group, a halogen or a substituted or unsubstituted C1-C5 alkyl group, R4 is a hydrogen atom, an alkoxy group, a halogen or a hydroxyl group, R5 is a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group, a nitroso group, a hydroxyl group, an acetyl group, an amino group or a halogen, R6 is a hydrogen atom, a substituted or unsubstituted C1-C5 alkyl group, an ester group, a carboxyl group or a hydroxyl group, and R7 is a hydrogen atom, a halogen, an amino group or a substituted or unsubstituted C1-C18 alkyl group; In formula B, R8 is a hydrogen atom, a hydroxyl group or an amino group, R9 is a hydrogen atom or a substituted or unsubstituted C1-C18 alkoxy group, R 10 is a hydrogen atom, a sulfonic acid group, a hydroxyl group or a halogen, R 11 is a hydrogen atom, a nitro group, an acetyl group or a halogen, R 12 is a hydrogen atom, a carboxyl group, a hydroxyl group or a sulfonic acid group, R 13 is a hydrogen atom, a substituted or unsubstituted C1-C18 alkyl group, a substituted or unsubstituted C1-C18 alkoxy group, an amino group, a halogen group or an aldehyde group, and R 14 It is a hydrogen atom, a hydroxyl group or a sulfonic acid group.
2. The passivation layer according to claim 1, characterized in that The interface modification material is selected from one or more of 1-naphthol, 2,3-dihydroxynaphthalene, 5-methyl-2-naphthol, 2-naphthol-6-sulfonic acid, 2-hydroxy-3-naphthoic acid, 2-hydroxy-6-naphthoic acid, 1-nitroso-2-naphthol, 1-bromo-2-naphthol, 1,6-dibromo-2-naphthol, 4-chloro-1-naphthol and 1-amino-2-naphthol-4-sulfonic acid.
3. The passivation layer according to claim 1, characterized in that The thickness of the passivation layer is 1-10 nm.
4. A method for preparing the passivation layer according to any one of claims 1 to 3, characterized in that: The method comprises: mixing an interface modification material and a solvent to obtain a passivation layer precursor solution, coating the passivation layer precursor solution, and then annealing to obtain a passivation layer.
5. The method according to claim 4, characterized in that The concentration of the interface modification material is 0.5-2 mg / mL.
6. The method according to claim 4, characterized in that The solvent is an anti-solvent, and the anti-solvent is selected from one or more of isopropanol, ethanol, ethyl acetate and ether.
7. The method according to claim 4, characterized in that The coating method is spin coating.
8. The method according to claim 4, characterized in that Annealing temperature is 80-100°C; and / or The annealing time is 5-10 minutes.
9. A perovskite solar cell comprising the passivation layer according to any one of claims 1 to 3.
10. The perovskite solar cell according to claim 9, characterized in that: The perovskite solar cell further includes a perovskite layer and an electron transport layer, and the passivation layer is between the perovskite layer and the electron transport layer.
Citation Information
Cited By
Method for optimizing interface layer and enhancing stability of perovskite solar cell
CN120805737A
Perovskite solar cell and preparation method thereof
CN122294699A